موديل رياضي لحساب طاقة الرياح وتحديد مؤشرات المزارع الريحية - حسن ياسر (Latakia University Journal -Engineering Sciences Series, 2019)
بسبب تزايد النشاط البشري في كافة مجالات الحياة، ازداد الطلب على مصادر الطاقة الإحفورية الآيلة إلى الزوال، يوماً ما وخصوصاً مع ازدياد أثارها البيئية السيئة، كزيادة انبعاث الغازات الضارة، ومنها CO2 ثاني أوكسيد الكربون ودوره في مشكلة الانحباس الحراري، لذلك كان لابد من البحث عن طاقة دائمة، ونظيفة مما استدعى التفكير بمصادر بديلة للطاقة تلك التي لا تنضب ومن أهمها الطاقة الشمسية وما ينتج عنها من طاقة الرياح وغيرها من أنواع الطاقات المتجددة التي تسمح بتغطية الطلب المتزايد على الطاقة مع أقل التأثيرات السلبية على البيئة، لذلك فإن هذا البحث يعتبر من الدراسات المتعلقة بإمكانية الاستفادة من طاقة الرياح، حيث يعرض طريقة لحساب احتياطي تلك الطاقة انطلاقاً من توافر المعطيات الكاملة عن أنظمة الرياح في منطقة معينة كما يوفر إمكانية تحديد المؤثرات الرئيسة للمزارع الريحية عله يكون جهداً متواضعاً من الجهود المكرسة للاستفادة من الطاقات البديلة في وقت أصبحنا أحوج ما نكون إليها. With the increasing human activity in significantly different walks of life, the demand of energy is the increasing and despite the fact that traditional sources of energy is still prevailing at the present time. The reserve sources of fossil fuel agent to force add to the growing negative environmental impacts resulting from the use of fuels such as increased emission of harmful gases, including CO2 carbon dioxide and its role in the problem of global warming. All this requires thinking about alternative sources of energy that is inexhaustible and the most important solar energy and the resulting wind power and other types of renewable energies, which would cover the growing demand for energy with less impact negative effects on the environment. So, this research is one of the studies of the potential benefit of wind energy, where a method for a reserve account that energy from the available data full systems. Wind in a certain area also provides the ability to determine the effects the main station wind power probably be modest effort of the efforts devoted to the use of alternative energy at a time when we urgently need to be.